Expanding access to healthcare for people who use drugs and sex workers: hepatitis C elimination implications from a qualitative study of healthcare experiences in British Columbia, Canada - Nance E. Cunningham; Jessica Lamb; Amanda Staller; Mel Krajden; Robert S. Hogg; Angela Towle; Viviane Dias Lima; Kate Salters (BMC, 2024)
Abstract Background Hepatitis C virus (HCV) is a major health threat in Canada. In British Columbia (BC) province, 1.6% of the population had been exposed to HCV by 2012. Prevalence and incidence of HCV are very high in populations of people who use drugs (PWUD) and sex workers (SW), who may experience unique barriers to healthcare. Consequently, they are less likely to be treated for HCV. Overcoming these barriers is critical for HCV elimination. This research sought to explore the healthcare experiences of PWUD and SW and how these experiences impact their willingness to engage in healthcare in the future, including HCV care. Methods Interpretive Description guided this qualitative study of healthcare experiences in BC, underpinned by the Health Stigma and Discrimination framework. The study team included people with living/lived experience of drug use, sex work, and HCV. Twenty-five participants completed in-depth semi-structured interviews on their previous healthcare and HCV-related experiences. Thematic analysis was used to identify common themes. Results Three major themes were identified in our analysis. First, participants reported common experiences of delay and refusal of care by healthcare providers, with many negative healthcare encounters perceived as rooted in institutional culture reflecting societal stigma. Second, participants discussed their choice to engage in or avoid healthcare. Many avoided all but emergency care following negative experiences in any kind of healthcare. Third, participants described the roles of respect, stigma, dignity, fear, and trust in communication in healthcare relationships. Conclusions Healthcare experiences shared by participants pointed to ways that better understanding and communication by healthcare providers could support positive change in healthcare encounters of PWUD and SW, who are at high risk of HCV infection. More positive healthcare encounters could lead to increased healthcare engagement which is essential for HCV elimination.